SOCIOPRENEURSHIP EMPOWERMENT AS A DEVELOPMENTAL POLITIC OF ISLAMIC BOARDING SCHOOL: A LESSON FROM DARUL MURSYID - Heri Kusmanto; Muryanto Amin (Universitas Negeri Medan, 2022)
This study analyses the sociopreneurship empowerment model performed by an Islamic boarding school from the perspective of developmental politics. Darul Mursyid boarding school, an Islamic education institution in the Sipirok district in North Sumatera, has been known to employ this model as a part of its social development efforts in giving economic and social benefits to the Sipirok society. This study was carried out through subsequent descriptive-qualitative research, observation, in-depth interview, and FGD (forum group discussion) methods. The results exhibited that most of the sociopreneurship efforts had been directed at producing agroforestry commodities such as coffee, vanilla, honey, vegetables, etc., along with other economic activities. The existence of Darul Mursyid boarding school greatly supported the financial capabilities of the community. Overall, the findings of this study revealed the critical role of Darul Mursyid's Islamic principles and the founding figures in driving the enhanced sociopreneurship empowerments. This outcome also implicitly exhibited the significant role of Islamic boarding schools despite civil organizations contributing a lot of benefits to society's welfare.Keywords: Development of Politics, Sociopreneurships, Empowerment, Islamic Boarding School, Darul Mursyid